Randomized Controlled Trial of Hyalobarrier® Versus No Hyalobarrier® on the Ovulatory Status of Women with Periovarian Adhesions: A Pilot Study. Issue 1 (January 2017) - Cheong, Ying; Bailey, Sarah; Forbes, Jane
Abstract Introduction Periadnexal adhesions are known to contribute to subfertility. The restoration of the tubo-ovarian anatomy is one the key principles in reproductive surgery, and this involves adhesiolysis. However, adhesion formation/reformation is very common after periovarian adhesiolysis. It is not known if the application of Hyalobarrier®, an anti-adhesion gel, around the adnexal region postsurgery influences ovulatory status. The study is a pilot randomized controlled trial (RCT) randomizing women into the application of Hyalobarrier® versus no Hyalobarrier® at the time of laparoscopy, where postsurgical ovulatory status and pregnancy rates were evaluated. Methods This was a pilot RCT where women were recruited from the gynecological and subfertility clinic who were deemed to require an operative laparoscopy. If intraoperatively they were found to have periovarian adhesions, they were randomized into having adhesiolysis with and without usage of Hyalobarrier® . Demographic details and intraoperative details including the severity, extent, and the ease of use of Hyalobarrier® were recorded. Prior to the surgery and postoperatively, the participants had their serum hormonal status (day 2 FSH, LH and day 21 progesterone) evaluated. Postoperatively, they underwent a follicular tracking cycle at 3 months. Results Fifteen women were randomized into use of Hyalobarrier® (study group) and 15 into the no Hyalobarrier® group (control group) between December 2011 and January 2014. There was no difference in the patient characteristics in terms of age, BMI, the number of previous pregnancies, or the extent, site, and severity of adhesions between the two groups. There was no significant difference between the study versus control groups in terms of the hormonal profile (day 2 FSH and day 21 progesterone) before or after surgery. The 3-month postoperative day 10–12 follicular tracking findings and endometrial thickness were similar between the study and control groups. Four women were pregnant in the study group (24%) and one in the control group (7%) cumulatively over 2 years. Conclusion The use of Hyalobarrier® post salpingo-ovariolysis did not influence follicular development as inferred from the results of the day 21 progesterone and folliculogram on day 10–12 3-month postsurgery. Trial Registration ISRCTN number, ISRCTN1833588. Funding Nordic Pharma.